2002
DOI: 10.1080/00102200290021353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygenate additives on polycyclic aromatic hydrocarbons(pahs) and soot formation

Abstract: Effects of three oxygenate additives (methanol, ethanol, and MTBE) on the formation of polycyclic aromatic hydrocarbons (PAHs) and soot in laminar, premixed, atmospheric pressure, fuel-rich flames of n-heptane were studied at an equivalence ratio of 2.10. A heated quartz microprobe coupled to online gas chromatography=mass spectrometry was used to establish the identities and absolute concentrations of major, minor, and trace species by the direct analysis of samples withdrawn from the flames. Benzene was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…All of these compounds have very low sooting tendencies as pure fuels [13]. Also, the role of oxygen-containing compounds as fuel additives was investigated by different research groups [3,7,[14][15][16][17]. Wu et al [18] studied the effect of ethanol addition to premixed ethylene-air flames.…”
Section: Introductionmentioning
confidence: 99%
“…All of these compounds have very low sooting tendencies as pure fuels [13]. Also, the role of oxygen-containing compounds as fuel additives was investigated by different research groups [3,7,[14][15][16][17]. Wu et al [18] studied the effect of ethanol addition to premixed ethylene-air flames.…”
Section: Introductionmentioning
confidence: 99%
“…The output parameter was the total PAH mole fraction, which includes the sum of the mole fractions of seven PAH compounds: naphthalene, acenaphthylene, phenanthrene, 4H-cyclopenta[def]-phenanthrene, fluoranthene, pyrene, and cyclopenta[cd]pyrene. Benzene was the most abundant aromatic compound and acenaphthylene and naphthalene were the most abundant PAH compounds in all the flames studied [18]. Fifty-four data sets obtained from six flames were divided into three groups: training, cross-validation, and testing, each containing 30 (∼ 56%), 6 (∼ 11%), and 18 (∼ 33%) sets, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the experimental setup used for data acquisition have been given elsewhere [17,18]. Therefore, only a brief description will be presented here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested several factors causing this phenomenon including the enhanced combustion efficiency, improved PAH oxidization of forming precursors due to increased oxygenation, dilution effect which reduces fuel PAH content, and absence of aromatic content in the biodiesel (Chang et al, 2014a). Furthermore, studies have reported that fuel at optimum conditions enhances chemical reactions of unsaturated hydrocarbons, which are precursors responsible for PAH emissions that may reduce total PAH emissions (Inal and Senkan, 2002;Cheruiyot et al, 2015). For EURO II, the total BaP eq were 2.17, 0.463, 0.337, and 0.353 µg BaP eq Nm -3 for 0, 20,000, 40,000, and 60,000 km, respectively, as shown in Table 5.…”
Section: Euro II Enginementioning
confidence: 99%